THE INFLUENCE OF PROMOTION, BRAND AWARENESS, AND BRAND AMBASSADORS ON PURCHASE DECISIONS ON THE SHOPEE MARKETPLACE: (Case Study of the Community of Jogosari Village, Pandaan District, Pasuruan Regency) - Meilinda Chusnul Utari; Sri Nuringwahyu; Dadang Krisdianto (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine the effect of promotion, brand awareness, and brand ambassadors on purchasing decisions in the Shopee marketplace. This research method is quantitative with 100 respondents in Jogosari Village, Pandaan District, Pasuruan Regency with incidental sampling technique. Data analysis used multiple linear regression with the help of SPSS version 24 for windows. Based on the research results, the promotion variable has a significant effect on purchasing decisions (tstatistic 2.128 > ttable 1.984984). The brand awareness variable has a significant effect on purchasing decisions with a value (tstatistic 2.396 > ttable 1.984984). However, the brand ambassador variable has no significant effect on purchasing decisions (tstatistic 0.055 < ttable 1.984984).